A Study on Barriers and Challenges to Value Management Implementation by Qs Firms in Selangor - Thien, Yung Wei; Sam, Man Keong (2016)
Malaysian government has realized that it is a must to modernize the Malaysian construction industry to keep in line with the modern technology such is BIM (Building Information Modelling) or knowledge such as value management. It is aids to ensure the long term health growth of Malaysian construction industry. Value management was highlighted with the establishment of Institute of Value Management Malaysia in 2000 with help and encouragement from government agencies such as Professional Services and Development Corporation (PSDC). [1] From the literature reviews that had been carried out, it was found out that the consultancy QS in the industry are short of knowledge and awareness on the benefit of value management. Therefore, a study was carried out to determine the barriers and challenges to value management implementation. This research was conducted at Selangor through online survey and in-depth interview. Descriptive survey method and statistical tools such as Statdisk and Minitab were used for the data analysis part.From this study, the degree of understanding of value management of QS in Selangor was at the average level. The main barriers which impede the implementation of value management are lack of knowledge and practice in value management and short of trained professionals in value management. The strategies to increase the application of value management had been developed from the data analysis too.